Konflik dan Resolusi: Peristiwa Berdarah di Tapanuli Masa Revolusi - Silaban, Edward; Suprayitno, Suprayitno; Nuhung, Nuhung (Jurnal Sejarah Citra Lekha, 2023)
After the proclamation of Indonesian independence on August 17, 1945, the resistance to the formation of the Republic of Indonesia among local rulers in East Sumatera, including the kings in Tapanuli, revealed the opposite. The kings and sultans was still adamant in maintaining their position and did not want to switch from an autocracy system to a democratic system because during local rulers were given many special privileges by the Dutch. Utilizing historical methods encompassing heuristic, verification, interpretation and historiography, as well as using the concept of revolution, to reveal causes and trajectory of the bloody events in Tapanuli during the Revolution. This study reveals that the violent incident in Tapanuli was driven by the Pesindo troops and the unionist from East Sumatra targeting the local kings. The resolution of the bloody conflict involved Tentara Repiblik Indonesia (TRI) and also traditional reconciliation as well as traditional reconciliation practices such as buffalo slaughtering and communal feasting.